Who will cast the first stone - Sumar, Sabiha; Jamal, Ahmed A. (New York Cinema Guild, 1988)
A documentary look at the impact of Islamization on women in Pakistan, showing the oppression and injustice which led Pakistani women to the forefront of the political struggle for equal rights.
Editor, Lynda J. Fowke.
Keywords: Women's rights -- Pakistan; Women in politics -- Pakistan; Women in Islam